HUBUNGAN KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR MAHASISWA D-III KEBIDANAN DI UNIVERSITAS BATAM - Sari, Rahayu Chamelia; Sulistyawati, Tri Ribut (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2019)
Â Emotional intelligence includes different but complementary abilities with academic intelligence. People will not be able to use their cognitive abilities according to their maximum potential without having emotional intelligence. This study aims to determine the relationship of intelligence with student achievement. This research is a quantitative research with cross sectional approach implemented in April-May 2017, the population is D-III Obstetrics University of Batam level I and II (62 people) with sampling technique Total Sampling. Then in the analysis using Chi Square test. The result of the research is the majority of students have a very good level of intelligence of 57 people (91.9%), student achievement index has a satisfactory achievement index of 58 people (93,5%) with p value 0,00,0,05. There is a relationship between emotional intelligence and student achievement. Suggestions are expected for students to be able to maintain emotional intelligence in order to influence learning achievement becomes much better.